The Increasing Interest in Dental and Oral Health Through Pop Up Castle Media as an Effort to Prevent The Spread of Caries Among School Children - Hadi, Sunomo; Alifia, Nadia Agda; Ayomi, Diasta; Ananta, Indriyani; Husni Abdillah, Ishraf Muhammad; Antika, Saroya Rindi (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Early childhood is the most appropriate time to instill values to instill positive behavior in children. Prevention of caries in children needs to be instilled early on seeing the impact of caries which can interfere with chewing function which leads to a lack of nutritional intake received by children. Prevention of caries can be done by maintaining dental health, one of which is done by brushing teeth. By brushing your teeth, you can maintain the cleanliness and strength of your teeth, but the wrong way of brushing cannot maximize oral hygiene. Therefore, knowledge of how to brush teeth properly and correctly is needed, in order to improve the quality of oral hygiene to the maximum. Making innovative media is very useful for increasing knowledge and attracting school-age children to pay attention to oral health. The author makes media in the form of a popup castle as an effort to prevent rampant caries in school-age children so that this media can make it easier for school-age children to understand efforts to maintain oral health. Objective: To describe the increase in school-age children's interest in maintaining oral health and hygiene by using castle popup media. Methods: The method we use in this counseling is game-based learning. The game method that we use is also based on the media that we offer in the form of a pop-up castle where in this media there are several materials including foods that are good for dental health and how to brush teeth properly and correctly and the right time to brush teeth. The game that we apply aims to review the material that has been explained during counseling. Results: 1) There is an increase in the knowledge of fourth grade students of SD Islam Maryam about oral health. 2) There is an increase in the interest of school-age children in maintaining oral health and hygiene by using castle popup media. 3) There is an improvement in the oral health status and behavior (knowledge, attitudes and actions) of elementary school students so that it can support general health. 4) This counseling activity is effective because it uses castle pop up media with a predetermined design and dental phantom so that the message conveyed can be understood by the target. 5) The final report and article will be included as a scientific publication in an accredited journal after the service. 6) The weakness of this activity is that it does not use other conventional counseling as a comparison.